Hybrid InGaAs quantum well–dots nanostructures for light-emitting and photo-voltaic applications. (2nd September 2015) - Mintairov, S A; Kalyuzhnyy, N A; Lantratov, V M; Maximov, M V; Nadtochiy, A M; Rouvimov, Sergei; Zhukov, A E
Abstract: Hybrid quantum well–dots (QWD) nanostructures have been formed by deposition of 7–10 monolayers of In0.4 Ga0.6 As on a vicinal GaAs surface using metal–organic chemical vapor deposition. Transmission electron microscopy, photoluminescence and photocurrent analysis have shown that such structures represent quantum wells comprising three-dimensional (quantum dot-like) regions of two kinds. At least 20 QWD layers can be deposited defect-free providing high gain/absorption in the 0.9–1.1 spectral interval. Use of QWD media in a GaAs solar cell resulted in a photocurrent increment of 3.7 mA cm −2 for the terrestrial spectrum and by 4.1 mA cm −2 for the space spectrum. Diode lasers based on QWD emitting around 1.1 μ m revealed high saturated gain and low transparency current density of about 15 cm −1 and 37 A cm −2 per layer, respectively.